Rare and Challenging Tumor Entity: Phyllodes Tumor of the Prostate. (7th December 2009) - Bannowsky, Andreas; Probst, Andreas; Dunker, Helmut; Loch, Tillmann
Abstract : Cystic epithelial-stromal tumors of the prostate are rare, with 82 cases reported in literature. These cases have been published under a variety of diagnoses, including phyllodes tumor and prostatic stromal proliferation of uncertain malignant potential as well as a malignant tumor called "prostatic stromal sarcoma". We report a case of a 60-year-old man with the histological diagnosis of phyllodes tumor of the prostate in transurethral resection specimen.